2014
DOI: 10.1002/anie.201404946
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Carbophilic Addition of α‐Diazoesters through Ligand‐Controlled Gold Catalysis

Abstract: The chemoselective addition of arenes and 1,3-diketones to α-aryldiazoesters was achieved through ligand-controlled gold catalysis. Unlike a dirhodium catalyst (which promotes C(sp3)-H insertion and cyclopropanation) and a copper catalyst (which catalyzes O-H and N-H insertions), the gold catalyst with an electron-deficient phosphite as the ancillary ligand exclusively gave the carbophilic addition product, thus representing a new and efficient approach to form "carbophilic carbocations", which selectively rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
118
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(122 citation statements)
references
References 82 publications
2
118
1
1
Order By: Relevance
“…This strategy permits ready explorations of these reactive intermediates without resorting to hazardous and potentially explosive diazo ketone precursor, [3] and thereby facilitates the development of various versatile synthetic methods. [2, 4],[5] While terminal alkynes are most frequently oxidized to terminal gold carbene intermediates, regioselective oxidations of internal alkynes can be challenging, and often only one regioisomer could be accessed selectively based on structural biases and upon optimizations of catalyst, oxidant and other reaction conditions.…”
mentioning
confidence: 99%
“…This strategy permits ready explorations of these reactive intermediates without resorting to hazardous and potentially explosive diazo ketone precursor, [3] and thereby facilitates the development of various versatile synthetic methods. [2, 4],[5] While terminal alkynes are most frequently oxidized to terminal gold carbene intermediates, regioselective oxidations of internal alkynes can be challenging, and often only one regioisomer could be accessed selectively based on structural biases and upon optimizations of catalyst, oxidant and other reaction conditions.…”
mentioning
confidence: 99%
“…Isocyanide-assisted O-H insertion reactions of diazo-derived copper carbenoids were suggested to proceed via ylide formation with the imino-anhydride generated from the carboxylic acid-isocyanide coupling [1289]. A hindered phosphite gold complex proved highly selective for C-H insertion over O-H insertion or cyclopropanation in the reaction of α-diazo esters with phenol or other electron rich aromatic substrates [1290,1291]. Cyclopropanation using magnetically-removable copper plated iron nanoparticles was also reported [1292,1293].…”
Section: )mentioning
confidence: 99%
“…Xi et al reported (ArO) 3 PAuNTf 2 catalyzed carbophilic addition of α-diazoesters at para-position of phenol derivatives (Scheme 54) (91). Aniline also reacted albeit in low yield.…”
Section: Para C-h Activationmentioning
confidence: 99%